Choroidal thickness is associated with renal hemodynamics in essential hypertension. Issue 2 (15th January 2020) - Geraci, Giulio; Maria Zammuto, Marta; Vadalà, Maria; Mattina, Alessandro; Castellucci, Massimo; Guarrasi, Giulia; Nardi, Emilio; Maida, Carlo; Zanoli, Luca; Cillino, Salvatore; Cottone, Santina; Mulè, Giuseppe
Abstract: The choroid is the most vascularized structure of the eye and plays a central role in the development of the retinal vascular changes that occur in arterial hypertension. Changes of choroidal thickness (ChT) assessed by optical coherence tomography (OCT) technology could reflect the vascular complications of hypertension. Also, intrarenal hemodynamic damage, associated with endothelial dysfunction, demonstrated to be a good indicator of systemic morphofunctional arterial impairment. The aim of this study is to assess the relationship between ChT and renal hemodynamics in subjects with essential hypertension. Routine laboratory tests, clinical history, and physical examination, including blood pressure assessment, were performed in 90 subjects with essential hypertension. All patients underwent Doppler ultrasonographic evaluation of intra‐renal hemodynamics and OCT imaging to assess ChT. When subjects were divided in two groups based on renal resistive index (RRI), group I (RRI ≥ 75% percentile) showed significantly lower values of ChT than group II (RRI < 75% percentile) ( P  < .001). When divided in two groups based on the ChT median values, patients with lower ChT had significantly higher RRI values than those with ChT above the median values ( P  < .05). In multivariate model including age, eGFR, and other variables as confounding factors, RRI ≥ 75% was independently associated with ChT. ChT was significantly correlated with renal resistive index in subjects with essential hypertension, confirmed in multivariate analyses. This result could be referred to changes in vascular elastic properties that occur in retinal and intrarenal vascular system probably due to oxidative stress and endothelial dysfunction commonly found in early complications of hypertension.